A Rumor (Hoax) about Covid-19 - Devid Saputra (International Journal of Publication Unit (IUJP) Agus Salim Metro, 2019)
A rumor (hoax) about Covid-19 appears in community, not only in Indonesia but also around the world. The spread of Covid' rumors cause the increasing of restlessness around community. Many Covid-19 hoax rumors such as the origin of virus, the spread of virus, how to prevent, how to treatment, to how the government policies to control this virus. The covid rumor is not only make people restlessness, but also make the people lost their life. As social media user, we must use our digital platform intelligently, wisely and carefully. We must cross check about direct and indirect information kindly and looking for the truth. because in Islam there is a prohibition to spread uncertain information. Keywords : islam, rumor, hoax,